Yosano Akiko and The Tale of Genji Revised editon - Rowley, Gaye (Michigan Monograph Series in Japanese Studies, 2000)
Yosano Akiko (1878-1942) has long been recognized as one of the most important literary figures of prewar Japan. Her renown derives principally from the passion of her early poetry and from her contributions to 20th-century debates about women. This emphasis obscures a major part of her career, which was devoted to work on the Japanese classics and, in particular, the great Heian period text The Tale of Genji. Akiko herself felt that Genji was the bedrock upon which her entire literary career was built, and her bibliography shows a steadily increasing amount of time devoted to projects related to the tale. This study traces for the first time the full range of Akiko's involvement with The Tale of Genji. The Tale of Genji provided Akiko with her conception of herself as a writer and inspired many of her most significant literary projects. She, in turn, refurbished the tale as a modern novel, pioneered some of the most promising avenues of modern academic research on Genji, and, to a great extent, gave the text the prominence it now enjoys as a translated classic. Through Akiko's work Genji became, in fact as well as in name, an exemplum of that most modern of literary genres, the novel. In delineating this important aspect of Akiko's life and her bibliography, this study aims to show that facile descriptions of Akiko as a "poetess of passion" or "new woman" will no longer suffice.